Optical orthogonal code design using genetic algorithms - Ho, C.K.; Lee, S.W.; Singh, Y.P. (2001)
A construction technique for optical orthogonal codes (OOCs) using genetic algorithms (GAs) is proposed. The performance of the GA OOCs is compared to that of four existing OOCs. Results show that the GA OOCs have a lower probability of error.